LE ’ECLAIRE (MILLET ECLAIRE) WITH THE SUBSTITUTION OF MILLET FLOUR AS UTILIZATION OF LOCAL FOODSTUFFS - Sutriyati Purwanti, Pia Celestine (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study purpose 1) Find the right recipe for making Le’í‰claire 2) Knowing the community’s acceptance of Le’Eclaire 3) Le’Eclaire nutritional information. The object of this research is eclaire with millet flour substitution. The method using Research and Development (R & D), with a 4D model (Define, Design, Development and Dissemination). The results of this study: 1) The right recipe for making Le’Eclaire with 50% millet flour substitution. The technique for making Le’Eclaire is baking, packaging used plastic and paper cups 2) Community acceptance of Le’Eclaire products, the limited scale acceptance of products is offered with an overall average 3.73, for modification products with a yield 3.8. The level of wide-scale acceptance is seen with an overall average f 3.8. 3) Le’Eclaire nutritional information based on the proximate test, the nutrient content in 100 gr Le’Eclaire namely air 37.75%, ash 2.67%, protein 9.37%, fat 23.19%, fiber 7.16%, and carbohydrates 19.87%. Keywords: Millet Flour, Le’Eclaire, Proximat Test